2009
DOI: 10.1007/s00405-009-1106-5
|View full text |Cite
|
Sign up to set email alerts
|

Age dependence of otoacoustic emissions: the loss of amplitude is primarily caused by age-related hearing loss and not by aging alone

Abstract: The amplitude of otoacoustic emissions (OAE) is known to decrease with increasing age, but it is still unclear whether this is due to aging alone or to age-related hearing loss. This study describes the exploration of a large database (5,142 patients from 0.4 to 89.8 years) collected in a routine clinical testing. Reliable pure tone audiograms, transitory evoked otoacoustic emissions (TEOAE) and distortion product otoacoustic emissions (DPOAE) recordings were available from 5,424 ears without conductive loss, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…At least one report failed to see any age effect on DPOAE fine structure (He and Schmiedt 1996). The strong co-variation of hearing threshold and age has posed a vexing problem in determining aging influences on cochlear function in humans (e.g., Oeken et al 2000;Uchida et al 2008;Hoth et al 2010). When strict control for audiometric threshold has been employed in aged adults, the isolated effects of aging on the OAE have been difficult to observe (Stover and Norton 1993).…”
Section: Agingmentioning
confidence: 95%
“…At least one report failed to see any age effect on DPOAE fine structure (He and Schmiedt 1996). The strong co-variation of hearing threshold and age has posed a vexing problem in determining aging influences on cochlear function in humans (e.g., Oeken et al 2000;Uchida et al 2008;Hoth et al 2010). When strict control for audiometric threshold has been employed in aged adults, the isolated effects of aging on the OAE have been difficult to observe (Stover and Norton 1993).…”
Section: Agingmentioning
confidence: 95%
“…Hudspeth & Corey 1977), and a typically smaller reflection component generated by linear reflections from the DP place (2 f 1 – f 2 ). Others have also reported that older subjects show more significant reductions in DPOAE amplitude than amplitude of the transient-evoked OAE, another reflection-type emission (Hoth et al 2010). Otoacoustic emissions generated by nonlinear distortion in the cochlea may be impacted by aging more than OAEs arising from linear reflection.…”
Section: Introductionmentioning
confidence: 99%
“…TEOAEs are measured within the 0.5 kHz to 4.0 kHz frequency range, and use a brief pure tone stimulus, while DPOAEs include frequencies up to 8.0 kHz, and use two pure tones that are produced simultaneously [59,60]. Although it is known that the amplitude of OAEs decreases with increasing age and increasing hearing thresholds, OAEs are not optimal to use within the CGA, as the test is highly influenced by environmental noise [61,62].…”
Section: Screening Methods For Age-related Hearing Loss In Older Pmentioning
confidence: 99%